THE EFFECT OF DIFFERENT TREATMENT PROCESSESAGAINST THE CONTENT OF PROXIMATE ON EDIBLE MOLLUSC (Faunus ater) - Asfi, Widya Mustika; Ilza, Mirna; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of different treatment processes against the content of proximate onedible mollusc (Faunus ater) which included the proximate, knowing the optimal treatment process to be used in cooking of edible mollusc. This research was carried out in 2 stages, namely 1) Preparation of edible mollusc, 2) Proximate analysis of edible mollusc meat. The experimental method was used in this research with Completely Randomized Design (CRD), which consists of three levels of treatment with different precessing L1 (non processing), L2 (steaming) and L3 (boiling).  The result of the analysis indicated that differences of processing treatment affect to proximate content of edible mollusc and steaming processing was the best treatment in processing of edible mollusc with characteristics of moisture, ashprotein, fat content (WW) were 76.92%, 4.88%, 10.46%, 0.82%.Keywords : edible mollusc, proximate, boiling and steaming